Continuous positive airway pressure in the treatment of meconium aspiration syndrome - Dangriwal, Komal; Arora, Vivek; Narnolia, Pankaj; Dhawal, Ayushi (International Journal of Contemporary Pediatrics, 2025)
Background: Meconium aspiration syndrome (MAS) is a significant neonatal condition, often associated with meconium-stained amniotic fluid (MSAF), fetal distress and severe respiratory complications. Management involves various forms of respiratory support, with continuous positive airway pressure (CPAP) being an effective, non-invasive option. This study aimed to assess the outcomes of CPAP therapy in neonates with MAS and identify predictors of success and failure in a tertiary care setting. Methods: A descriptive observational study was conducted at the Paediatric Department of RNT Medical College, Udaipur, from January 2024 to July 2024. A total of 77 neonates with MAS were enrolled, with data collected on maternal complications, delivery mode, clinical status, and neonatal outcomes. CPAP was initiated in most cases, and its effectiveness was monitored. Results: Fetal distress was present most commonly in newborns with maternal complications (55.26%), followed by pregnancy-induced hypertension (19.74%). Most infants were born via C-section (42.1%), with a mean birth weight of 2.53 kg. CPAP was successful in 85.53% of cases, with predictors of success including lower Downe’s scores. Severe asphyxia was the leading cause of mortality (13.16%). Conclusions: CPAP is a highly effective treatment for moderate-to-severe MAS, offering advantages over mechanical ventilation in terms of reduced complications. Early initiation improves respiratory outcomes and reduces the need for invasive ventilation. Monitoring and early identification of risk factors, such as Downe’s score, are crucial for optimizing management.